How medical specialists experience the effects of a mindful leadership course on their leadership capabilities: a qualitative interview study in the Netherlands. Issue 12 (15th December 2019) - Vreeling, Kiki; Kersemaekers, Wendy; Cillessen, Linda; van Dierendonck, Dirk; Speckens, Anne
Abstract : Objectives: Medical leaders are facing leadership challenges that ask for a leadership style that takes care of both themselves and their coworkers. Mindfulness may support this leadership style. We explored how a 'Mindful leadership for medical specialists' course affected medical specialists' leadership. Design: We conducted a qualitative study based on in-depth interviews. The grounded theory method was used to analyse the data. Setting: A university medical centre in the Netherlands. Participants: Seventeen medical specialists (six male) with an average age of 51 years (ranging from 40 to 66 years). Interventions: The mindful leadership course consisted of 10-weekly 5-hour sessions that focused on cultivating mindfulness and compassion. In addition, sessions included didactic and interactional teaching about leadership theories. Results: Four categories emerged from the data: (A) Self - Attitude: psychological attitude towards self, (B) Self - Behaviour: behaviour towards self, (C) Other - Attitude: psychological attitude towards others, and (D) Other - Behaviour: behaviour towards others. Themes were defined within these categories: awareness of self, open mind, insight and appreciation of self (A), emotional and cognitive self-regulation, letting go of unhelpful behaviour and developing helpful behaviour (B), differences in attitude to others such as awareness of (impact on) others, keeping an open mind about others, allowing difficult emotions associated with others, appreciating of others (C), and communicating more effectively, providing direction, empowering and caring for others (D). Conclusions: The results help us understand the core elements of mindful leadership, both with respect to one's psychological attitude and behaviour towards oneself and others. More research on mindful leadership and the effects on self and others is needed. Mindful leadership courses could be a valuable part of clinical training and might contribute to more sustainable healthcare organisations.